So Much More Than Honour Killing: Reading The Duchess of Malfi - Kurian, Anna (Radical Teacher, 2025)
This teaching note demonstrates how John Webster's Duchess of Malfi continues to resonate in an Indian classroom of the 21st century. It focuses on the patriarchal systems within which the Duchess is embedded which make it impossible for her to do justice to either her personal or her princely duties, and in doing so it illumines the situation in which many 21st century Indian middle class women find themselves.